Radical din (×-3)²=7
![\sqrt{(x - 3) {}^{2} } = 7 \sqrt{(x - 3) {}^{2} } = 7](https://tex.z-dn.net/?f=+%5Csqrt%7B%28x+-++3%29+%7B%7D%5E%7B2%7D+%7D++%3D+7)
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
x = -4 ; x = 10
Explicație pas cu pas:
√(x-3)² = 7 <=> Ix-3I = 7 =>
x-3 = 7 => x = 10
-x+3 = 7 => x = -4
Răspuns de
1
Alte întrebări interesante
Matematică,
8 ani în urmă
Geografie,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă